RANCANG BANGUN DC-DC FLYBACK CONVERTER DENGAN MODE CCM (CONTINUOUS CONDUCTION MODE) UNTUK APLIKASI FUEL CELL - Ahmad Syafiq Kanzul Fikri; Waru Djuriatno; Panca Mudjirahardjo (Jurnal Mahasiswa TEUB, 2023)
Advances in technology and science are rapidly increasing the need for energy. In an effort to meet the increasing demand for energy, a qualified energy source is needed. The biggest source of energy today still comes from fossil fuels which must be reduced dependency to reduce global warming and prevent energy crises in the future. Therefore, a clean and renewable alternative energy source is needed which has great potential to be developed such as fuel cells. As an alternative energy, fuel cells still have problems with their low output DC voltage, so to support fuel cell performance a power electronics device is needed. The flyback topology is a relatively simple power electronics topology compared to other topologies for the low to medium power category. The advantage of the flyback topology is its ability to provide isolation between the input and load sections, with the presence of a transformer (coupled inductor) between the input and output sections. One of the operating modes of the flyback converter is the CCM (Continuous Conduction Mode) operation mode which has the advantage of having a smaller primary current value thereby reducing the conduction losses and switching losses of the flyback converter. This research was carried out by simulating and designing a flyback converter in CCM mode to increase the fuel cell voltage from 24 V to 72 V. In testing the DC-DC flyback converter close loop CCM mode using PI (Proportional Integral) control it has been able to increase the voltage from 24 V to 72 V constantly with an average power efficiency above 80%. The device also always works in CCM mode as indicated by the transformer primary current (Ip) waveform or MOSFET drain-source current (IDS) waveform which is in the shape of a trapezoid. Keywords: Fuel Cell, DC-DC Flyback Converter, Continuous Conduction Mode, Transformator, Coupled inductor, Proportional Integral, Close Loop